2016
DOI: 10.1111/medu.12944
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and review of learner performance and preference: virtual versus optical microscopy

Abstract: Although many individual studies have reported non-significant findings in comparisons of VM and OM, the enhanced power afforded by meta-analysis revealed that the pedagogical approach of VM is modestly superior to that of OM and is preferred by learners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 70 publications
3
40
0
Order By: Relevance
“…The protocol presented herein closely follows a procedure previously described by Wilson et al (2016). Four teams of paired researchers reviewed roughly one-quarter of all records retrieved.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…The protocol presented herein closely follows a procedure previously described by Wilson et al (2016). Four teams of paired researchers reviewed roughly one-quarter of all records retrieved.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…However, this may promote the tendency for students to undervalue the importance/existence of variation in tissue sections [14]. It has been suggested by Helle and colleagues [15] that learning using virtual microscopy results in greater learning gains for high-performing students, compared with lower-performing students.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are unsurprising, because activities that promote interaction and engagement with microscopic morphology are needed to improve learning outcomes, irrespective of the medium employed. Nevertheless, a meta-analysis of virtual microscopy using multiple standardised comparative studies concluded that, on balance, VM is superior to LM for learning [14]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In health professional education, literature reviews take increasingly diverse forms. For example, in this edition of Medical Education , there are meta‐analyses, systematic reviews, a thematic analysis and a critical synthesis in the form of an essay, a traditional form that is not always considered a literature review per se . Other common review types include integrative, realist and narrative reviews.…”
mentioning
confidence: 99%